PENGARUH MODEL PEMBELAJARAN JIGSAW TERHADAP MOTIVASI BELAJAR SISWA - Wulandari Wulandari; Hadi Gunawan Sakti (UNDIKMA, 2019)
Problem that occur at school in Indonesia language course, when teacher do teachingstill use conventional methods such as speech, discussions, and group work,that is make studentsless motivated in learning and then when the teacher delivering the material still uses chalk andblackboard,because it does not heaving an LCD projector at school. In this causes student be lessable to actively participate in the learning process of Indonesia language course. Purpose f thisresearch was to determine effect of Jigsaw Learning Model towards Student Learning Motivationto Indonesian language course in 7th Grade Studen,AL-Ahyar Nw Islamic Junior high School StateBagik Polak, West Lombok, 2018/2019 Academic Year. Research methode use experimentalmethode and research design One Group Pre-tes Pos-tes Design. Research population using in7thGrade Student with 115 student,because number of population using more than 100 student so inthis research using sample random sampling, withs sample of research use 28 studen totally. Datacollection method used was the questionnaire method white documentation as acomplementarymethod. Analyz sinthe chi square formula(x2). The results of the study are x2 count of 19.551 andthe value of x2 tables at a significant level of 5% with dk (fh-1)=2-1=1 greater than the value of x2in the table (19,551>15,507) which means that HO is rejected and Ha is accepted it means: Thereis an Efect of Jigsaw Learning Model toword Student Learning Motivation to Indonesia languagecaerse in 7th Grade student AL-ahyar NW Islamic Junior High School State Bagek Polak WestLombok Regency 2018/2019 Academic Year.”significant”